Cold Stress Resistance of Tomato (Solanum lycopersicum) Seedlings Is Enhanced by Light Supplementation From Underneath the Canopy - Lu, Tao; Song, Yangfan; Yu, Hongjun; Li, Qiang; Xu, Jingcheng; Qin, Yong; Zhang, Guanhua; Liu, Yuhong; Jiang, Weijie (Frontiers in Plant Science, 2022)
Abstract: Adverse environmental conditions, such as low temperature, greatly limit the growth and production of tomato. Recently, light emitting diodes (LEDs) with specific spectrum arespectra have been increasingly used in facility horticulturale production facilities. The chosen spectrum can affect the plant growth, development and resistance, but the physiological regulatoryion mechanisms are largely unknown. In this study, we investigated the effects of LED light supplementsupplementation (W: B=2:1, light intensity ofis 100 µmol·m-2·s-1, for 4 hours/day from 9:00-13:00) from above and below thedifferent positions of canopy leaves on the tomato resistance under sub-low temperature stress (LT, 15 °C /8 °C). The rResults showed that light supplementsupplementation from underneath the canopy (USL) promoted the growth of tomato seedlings, as the plant height, stem diameter, root activity and plant biomass were significantly higher than thatthose underof LT. And, the The activity of the photochemical reaction center was enhanced because of the increase in the maximal photochemical efficiency (Fv/Fm) and photochemical quenching (qP), which distributedmade more photosynthetic energy distributed to the photochemical reactionreactions and promoted photosynthetic performance [the maximum net photosynthetic rate (Pmax) was improved]. USL also advanced the degree of stomatal opening, thus facilitating carbon assimilation under LT. Additionally, the relative conductivity (RC) and malondialdehyde content (MDA) were decreased, while the soluble protein content and superoxide dismutase (SOD) activity were increased with the application of USL under LT, thereby causing thea reduction ofin membrane lipid peroxidation and alleviation of stress damage. These results suggest that light supplement from underneathsupplementation from underneath the canopy improves the cold- resistance of tomato seedlings mainly by alleviating photoinhibitonthe degree of photoinhibition on degree of photosystems, improving the activity of the photochemical reaction center, meanwhile by enhancingand enhancing the activities of antioxidant enzymes, thereby promoting the growth and stress resistance of tomato plants.